(untitled) (Physical Education, Health and Social Sciences, 2026)
Public sector development projects frequently underperform despite the widespread adoption of formal project management standards. In developing governance contexts, projects often experience cost escalation, schedule delays, implementation disputes, and limited post-completion utilization. While international project management frameworks acknowledge stakeholder management as a key knowledge area, stakeholder engagement is commonly implemented as a procedural communication activity rather than an embedded governance process. This paper develops a governance-based explanation of how structured stakeholder engagement contributes to multidimensional project success in public sector environments. Drawing upon stakeholder theory, project governance theory, and organizational communication literature, the article proposes that stakeholder engagement influences project performance indirectly through communication quality, while leadership and governance conditions determine the strength of this relationship. Using a mixed-method analytical design combining survey-based measurement and interpretive case evidence from public projects in Punjab, Pakistan, the paper conceptualizes stakeholder engagement as a performance-generating institutional capability rather than a peripheral management practice. The findings suggest that projects characterized by systematic stakeholder identification, participatory planning, and continuous feedback mechanisms demonstrate superior performance across efficiency, service adoption, and sustainability outcomes. The article contributes to project management scholarship by integrating governance and stakeholder perspectives into a single explanatory framework and by operationalizing engagement into measurable managerial practices suitable for public sector organizations.